2020
DOI: 10.1080/17461391.2020.1788647
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of energy availability and associated risk factors in professional female soccer players

Abstract: This study aimed to assess energy availability (EA), alongside possible risk factors of reduced or low EA of professional female soccer players during a competitive season. Thirteen players (age: 23.7 ± 3.4 y, stature: 1.69 ± 0.08 m, body mass: 63.7 ± 7.0 kg) engaged in a 5-day (two rest days, one light training, heavy training and match day) monitoring period. Energy intake (EI) and expenditure during exercise (EEE) were measured. EA was calculated and categorised as optimal, reduced or low (>45, 30-45, <30 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 47 publications
9
50
1
Order By: Relevance
“…When dietary energy availability is limited, key physiological processes such as the menstrual cycle are sacrificed to conserve energy, resulting in oligomenorrhea or amenorrhea, and greater injury incidence has been observed in athletes and military recruits with extended cycle durations (Rauh et al, 2010 ; Knapik et al, 2013 ). Moss et al ( 2020 ) showed that 23% of elite female footballers had low (≤ 30 kcal·kg·FFM −1 ·day −1 ) energy availability and menstrual dysfunction has been observed in 9.3–19.3% of elite footballers (Sundgot-Borgen and Torstveit, 2007 ; Prather et al, 2016 ). To date, the impact of extended menstrual cycle duration has not been explored in relation to injury risk.…”
Section: Introductionmentioning
confidence: 99%
“…When dietary energy availability is limited, key physiological processes such as the menstrual cycle are sacrificed to conserve energy, resulting in oligomenorrhea or amenorrhea, and greater injury incidence has been observed in athletes and military recruits with extended cycle durations (Rauh et al, 2010 ; Knapik et al, 2013 ). Moss et al ( 2020 ) showed that 23% of elite female footballers had low (≤ 30 kcal·kg·FFM −1 ·day −1 ) energy availability and menstrual dysfunction has been observed in 9.3–19.3% of elite footballers (Sundgot-Borgen and Torstveit, 2007 ; Prather et al, 2016 ). To date, the impact of extended menstrual cycle duration has not been explored in relation to injury risk.…”
Section: Introductionmentioning
confidence: 99%
“…Soccer players score lower than non-athlete controls on scores of disordered eating, and the proportion of self-reported eating disorders (5.9%) is lower than other sports and controls [128]. However, 8.0-19.3% of elite soccer players report menstrual dysfunction [129][130][131], a symptom of low EA. [129].…”
Section: Energy Availabilitymentioning
confidence: 92%
“…This suggests that opportunities for energy intake should be maximised on match and heavy training days to prevent a recurring pattern of sub-optimal EA. This was a consequence of dietary energy intake not matching energetic demands [129]. Collectively, it appears that the majority of incidence of low EA occurred when energy intake was not adjusted to the energetic demands of training or match-play.…”
Section: Energy Availabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…A previous study on Japanese male runners (19–21 years) has identified that a high risk of having low EA in this populations exists, leading to metabolic suppression and increased bone resorption ( Taguchi et al, 2020 ). Studies on professional female and male soccer players during training period provided the evidences that energy deficiency and low EA can be found in the different sports ( Moss et al, 2020 ; Reed et al, 2014 ; Russell & Pennock, 2011 ). These studies can support the IOC consensus statement on RED-S in male athletes with different ethnicities and sports background.…”
mentioning
confidence: 99%